Raw daily weather records from 7 IDEAM’s stations in Tolima and Meta departments, Colombia - Instituto de Hidrología, Meteorología y Estudios Ambientales (2016)
Weather records from 7 stations of IDEAM located in Tolima and Meta departments in Colombia. Five variables are available at daily scale: precipitation (prec), maximum temperature (tmax), minimum temperature (tmin), relative humidity (rhum), and sun bright (sbright). For units details, please consult variable_codes.txt For localization of the stations, please consult List_files.txt